Cis variants identified in F508del complex alleles modulate CFTR channel rescue by small molecules. Issue 4 (16th January 2018) - Baatallah, Nesrine; Bitam, Sara; Martin, Natacha; Servel, Nathalie; Costes, Bruno; Mekki, Chadia; Chevalier, Benoit; Pranke, Iwona; Simonin, Juliette; Girodon, Emmanuelle; Hoffmann, Brice; Mornon, Jean‐Paul; et al.
Abstract: Molecules correcting the trafficking (correctors) and gating defects (potentiators) of the cystic fibrosis causing mutation c.1521_1523delCTT (p.Phe508del) begin to be a useful treatment for CF patients bearing p.Phe508del. This mutation has been identified in different genetic contexts, alone or in combination with variants in cis . Until now, 21 exonic variants in cis of p.Phe508del have been identified, albeit at a low frequency. The aim of this study was to evaluate their impact on the efficacy of CFTR‐directed corrector/potentiator therapy (Orkambi). The analysis by minigene showed that two out of 15 cis variants tested increased exon skipping (c.609C > T and c.2770G > A). Four cis variants were studied functionally in the absence of p.Phe508del, one of which was found to be deleterious for protein maturation c.1399C > T (p.Leu467Phe). In the presence of p.Phe508del, this variant was the only to prevent the response to Orkambi treatment. This study showed that some patients carrying p.Phe508del complex alleles are predicted to poorly respond to corrector/potentiator treatments. Our results underline the importance to validate treatment efficacy in the context of complex alleles. Abstract : The functional defect of the main cystic fibrosis causing mutation p.Phe508del can be partially alleviated by compounds acting on the folding (correctors) and/or gating (potentiators) of the mutant p.Phe508del‐CFTR protein. Here we show that two cis mutations alter normal exon splicing and one mutation reduces channel maturation, hindering treatment efficacy. Our results underline the necessity to validate in‐vitro treatment efficacy in the context of complex alleles.